Effect of iron fortification and prebiotics on iron biomarkers in anemic rats - S. Iqbal; S. Zafar; W. Ahmed; S. H. B. U. Shah; J. Abid; U. Farooq; A. M. R. Ahmad (Brazilian Journal of Biology)
Abstract One of the biggest public health problems globally is that of iron deficiency anemia. The present research aimed to determine the effect of prebiotics along with iron fortification on iron biomarkers in female anemic rats as some evidence suggests that prebiotics convert increase the solubility of iron, thereby enhancing its absorption. A total of 126 Sprague Dawley rats were fed with sixteen different types of fortified feed containing prebiotics (Inulin + Galacto Oligosaccharides) and Iron Fortificants (Sodium Ferric Ethylenediaminetetraacetate + Ferrous Sulphate). The duration of the trials was 3 months aimed at determining the effect of iron fortification and prebiotics on different iron biomarkers including Hemoglobin (Hb), Hematocrit, Red Blood Cell (RBC) count, Mean Corpuscular Volume (MCV), Mean Corpuscular Hemoglobin (MCH) and Mean Corpuscular Hemoglobin Concentration (MCHC). The trials resulted in statistically significant improved iron biomarkers among female anemic rats (P-value < 0.05). It was concluded that iron fortification and prebiotics in combination were able to increase the levels of iron biomarkers in female anemic rats.